Sports nutrition strategies for success : a practical guide to improving performance through nutrition - Larson, Abigail J.; Woodruff, Kary (Health, wellness, and exercise science collection., 2017)
"This text provides science-based nutrition recommendations that support the optimal performance and well being of young athletes. The authors give an overview of sports nutrition fundamentals, including a breakdown of the macronutrient, micronutrient, and hydration recommendations, as well as optimal quantity and timing of nutrient intake. They also discuss weight management and how to support athletes in achieving healthy weight gain or weight loss; disordered eating and eating disorders signs, symptoms, and treatment; and risks and benefits of dietary supplements. This text concludes with delicious and nutritious meal and snack recipes and a list of reputable resources. Ultimately, this text is a practical, meaningful, and applied sport nutrition resource for exercise professionals across a wide range of disciplines."--Page 4 of cover